In vi(vi)no veritas? Expertise, review accuracy and reputation inflation - Rebecca Janßen; Matthew K. Ribar (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Review systems including quantitative measures as well as text-based expression of experiences are omnipresent in today's digital platform economy. This paper studies the existence of reputation inflation, i.e. unjustified increases in ratings, with a special focus of heterogeneity between experienced and non-experienced users. Using data on more than 5 million reviews from an online wine platform we compare consistency between numerical feedback and textual reviews as well as sentiment measures. We show that overall the wine platform displays strongly increasing numerical feedback over our time period from 2014 to 2020 while this is not the case for our control measures. This gap appears to be even stronger for users with less experience or expertise in wine reviewing. We conclude, that online platforms as well as potential customers should be aware of the phenomenon of reputation inflation and simplifying feedback to one number might do a disservice to review platforms' goal of providing a representative quality assessment.
Keywords: C53; D02; L15; L81; 330; reputation inflation; online reviews; expert reviews; sentiment; text data